Kepuasan dan Loyalitas sebagai Mediator Experiential Marketing terhadap WOM - Sastra, I Wayan Eka Darma; Prianthara, Ida Bagus Teddy (Studi Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: The purpose of this research is to investigate how experiential marketing affects word-of-mouth (WOM), using customer loyalty and satisfaction as mediating factors. The research was conducted at Sastra Barbershop Payangan, representing the growing male grooming industry in Bali. Methodology: The research applied a quantitative approach using incidental sampling of 135 respondents, who were customers of Sastra Barbershop. Data were collected through questionnaires measured on a five-point Likert scale. Results: The findings show that experiential marketing has a positive and significant impact on customer satisfaction, customer loyalty, and word of mouth. Customer satisfaction also positively affects customer loyalty and WOM, while customer loyalty significantly enhances WOM. Moreover, both customer satisfaction and customer loyalty partially mediate the relationship between experiential marketing and WOM, with a double mediation effect strengthening this relationship. Conclusions: This study concludes that experiential marketing is a critical driver in shaping customer behavior. By creating memorable experiences, barbershops can increase satisfaction, foster loyalty, and amplify WOM. The mediating roles of satisfaction and loyalty emphasize that experiential marketing does not work in isolation but operates through psychological and emotional bonds formed with customers. Limitations: This study was limited to one case, Sastra Barbershop Payangan, with 135 respondents. Thus, the findings may not be generalized across other service industries or regions. Contribution: This study contributes theoretically by reinforcing the role of experiential marketing in strengthening customer satisfaction, loyalty, and WOM within service marketing literature.